"Heart-Rending Ambivalence": Jacques Maritain and the Complexity of Postwar Catholic Philosemitism - Crane, Richard Francis (Studies in Christian-Jewish relations, 2011)
Philosopher Jacques Maritain (1882-1973) embraced a quest for sanctity at the core of his vocation as a French Catholic intellectual. Known as an exponent of the teachings of Saint Thomas Aquinas, he also devoted considerable energies to the promotion of democracy and human rights, as well as the combat against antisemitism. Maritain has been lauded for his sometimes courageous attempts to eradicate anti-Jewish prejudice from the Christian conscience, though some prevailing interpretations oversimplify this thinker's motivations and ideas. Keeping in mind the historically-contingent and often ambivalent nature of philosemitism, this article analyzes Maritain's postwar writings on the Jewish Question and his interactions with Popes Pius XII and Paul VI, Anglican theologian James Parkes, Jewish historians Leon Poliakov and Jules Isaac, and fellow Catholic writers Paul Claudel and Francois Mauriac.